2022
DOI: 10.15283/ijsc22008
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion to Achieve Glial Cell Fates: Oligodendrocytes and Schwann Cells

Abstract: Glia have been known for its pivotal roles in physiological and pathological conditions in the nervous system. To study glial biology, multiple approaches have been applied to utilize glial cells for research, including stem cell-based technologies. Human glial cells differentiated from pluripotent stem cells are now available, allowing us to study the structural and functional roles of glia in the nervous system, although the efficiency is still low. Direct conversion is an advanced strategy governing fate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…However, our study has limitations of oversimplifying the complex interaction between developing immature gut and differentiating peripheral neurons. The enteric nervous system in the colon is composed of various types of neurons and enteric glial cells ( 36 ), forming complex neural networks in the submucosal and myenteric plexuses ( 37 ). To clarify the impact of interactions between immature organoids and developing neurons on the functional maturation of the gut epithelium and the functional specification of neural cells, it is necessary to differentiate the various types of neural cell constituents and conduct further investigations into the precise mechanisms underlying nonsynaptic transmission of substance P.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study has limitations of oversimplifying the complex interaction between developing immature gut and differentiating peripheral neurons. The enteric nervous system in the colon is composed of various types of neurons and enteric glial cells ( 36 ), forming complex neural networks in the submucosal and myenteric plexuses ( 37 ). To clarify the impact of interactions between immature organoids and developing neurons on the functional maturation of the gut epithelium and the functional specification of neural cells, it is necessary to differentiate the various types of neural cell constituents and conduct further investigations into the precise mechanisms underlying nonsynaptic transmission of substance P.…”
Section: Discussionmentioning
confidence: 99%
“…Besides embryonic, induced, or adult tissue-derived stem cells, in vitro Schwann cell differentiation has used human [ 119 , 177 , 224 , 225 , 226 , 227 , 228 ] and rodent [ 177 , 223 ] skin fibroblasts via direct conversion methods, bypassing the pluripotency stage (reviewed by Yun et al, 2022 [ 283 ]). In most studies, conversion of fibroblasts was achieved by introducing transcription factors driving neural crest and/or Schwann cell fate, mostly Sox10 [ 119 , 227 ] in combination with Krox20 (also known as Egr2) [ 177 , 226 ], and subsequent culture in Schwann cell differentiation medium containing combinations of Nrg1, forskolin, PDGF, db-cAMP, CNTF, bFGF, and FBS.…”
Section: In Vitro Differentiation Of Schwann Cellsmentioning
confidence: 99%
“…Although a transgenic mouse model expressing human ACE2 indicated that SARS-CoV-2 infection occurred only in epithelial cells, not olfactory neurons [30], the results of the direct infection of hPSC-derived peripheral neurons with SARS-CoV-2 [31], along with autopsy data [26,79,80], still presents a potential nerve track for viral spread through synaptic transmission. In order to overcome the limitations of animal or cell-based research, studies using mature brain organoids with the concept of a neuronal assembloid are required in the near future [71,81,82].…”
Section: Central Nervous System Organoidsmentioning
confidence: 99%